Pengaruh Kebijakan Dividen, Kebijakan Hutang Dan Keputusan Investasi Terhadap Nilai Perusahaan Pada Pt Adaro Energy Tbk Periode 2014-2023 - Reza Octovian; Rismayanti Rismayanti (Journal of Innovative and Creativity, 2025)
This study, which utilized an associative quantitative approach on PT Adaro Energy Tbk's financial reports from 2014-2023, examined the effect of dividend policy (DPR), debt policy (DER), and investment decisions (PER) on company value (Tobin's Q). The findings from multiple linear regression analysis reveal that debt policy (DER) has a significant positive effect on company value, as evidenced by a t-statistic of 3.173 and a significance value of 0.019. Conversely, both dividend policy (DPR) and investment decisions (PER) were found to have no significant effect on company value. The study also concluded that the three variables simultaneously do not significantly influence company value. With an R2 of 0.634, the model suggests that 63.4% of the variation in company value can be attributed to these three factors, while the remaining 36.6% is explained by other variables. The primary recommendation is for the company's management to focus on optimizing their debt structure to enhance company value.